Migration and remittances during the global financial crisis and beyond - Sirkeci, İbrahim; Cohen, Jeffrey H. (Jeffrey Harris); Ratha, Dilip (World Bank e-Library., 2012)
During the 2008 financial crisis, the possible changes in remittance-sending behavior and potential avenues to alleviate a probable decline in remittance flows became concerns. This book brings together a wide array of studies from around the world focusing on the recent trends in remittance flows. The authors have gathered a select group of researchers from academic, practitioner and policy making bodies. Thus the book can be seen as a conversation between the different stakeholders involved in or affected by remittance flows globally. The book is a first-of-its-kind attempt to analyze the effects of an ongoing crisis on remittance flows globally.